What eyes behold if missed can be a life taking event: a case of orbital cellulitis. - Reza MQ,; Johar MJ,; Ismail MS, (Penerbit UKM, 2013)
must be distinguished from preseptal cellulitis. It is an infective process involving ocular adnexal structures posterior to the orbital septum. High index of suspicion is the key to its diagnosis as even experienced physician can miss. Here, we present a case of a 15-year-old female who presented with progressive swelling over right forehead associated with high grade fever, headache and purulent discharge of the swelling. She was diagnosed with sepsis due to right forehead abscess and was treated with intravenous antibiotics followed with admission. However, she suddenly deteriorated in the ward which required intubation and thereby Intensive Care Unit (ICU) admission. Investigations revealed fluid collection at right retrobulbar space suggestive of an abscess where emergency drainage was carried out. Unfortunately, her condition worsened and patient succumbed at day-10 of admission, despite all efforts.